Study of relay position in two-path successive relaying with interference cancellation - Qian, Yu Liau (2014)
Two-path successive relaying scheme is designed to recover the loss of spectral efficiency due to half-duplex constraint When not operating in orthogonal channels, the relay pair used in the successive relaying scheme interferes each other. This inter-relay interference degrades the capacity performance of the successive relaying scheme significantly. Successive interference cancellation has been proposed to tackle the inter-relay interference in two-path successive relaying. The effectiveness of such interference cancellation technique relies heavily on the instantaneous channel conditions, which is not only depending on the small scale fading but also the large scale path loss. However, in the existing literature of two-path successive relaying, the effect of path loss and the position of relays have not been considered. Therefore, in this paper, we study the effect of path loss and relay position to the ergodic capacity of the two-path successive relaying with and without interference cancellation. We also compare the performance of successive relaying with the conventional half-duplex relaying. Simulation results show that the ergodic capacity of the two-path successive relaying not only depends on the relative position of the relays from source and destination nodes, but it is also affected by the inter-relay distance. When the relays are relatively closer to the destination and the inter-relay distance is short, the ergodic capacity of the two-path successive relaying with interference cancellation outperforms the conventional half-duplex relaying.